Decorin-Binding Protein of Borrelia burgdorferi Is Encoded within a Two-Gene Operon and Is Protective in the Murine Model of Lyme Borreliosis - Hagman, Kayla E. (American Society for Microbiology, 1998)
Isolated outer membranes of Borrelia burgdorferi were used in immunoblotting experiments with sera from immune mice to identify new putative Lyme disease vaccine candidates. One immunoreactive polypeptide migrated on polyacrylamide gels just proximal to outer surface protein C and comigrated with [(3)H]palmitate-labeled polypeptides. A degenerate oligonucleotide primer based upon internal amino acid sequence information was used to detect the corresponding gene within a B. burgdorferi total genomic library. The relevant open reading frame (ORF) encoded a polypeptide comprised of a 24-amino-acid putative signal peptide terminated by LLISC, a probable consensus sequence for lipoprotein modification, and a mature protein of 163 amino acids. Immunoblots of a recombinant fusion protein corresponding to this ORF supported the idea that the encoded protein was a previously reported decorin-binding protein (DBP) of B. burgdorferi N40 (B. P. Guo, S. J. Norris, L. C. Rosenberg, and M. Höök, Infect. Immun. 63:3467–3472, 1995). However, further DNA sequencing revealed the presence of a second ORF, designated ORF-1, whose termination codon was 119 bp upstream of the dbp gene. ORF-1 also encoded a putative lipoprotein with a mature length of 167 amino acids. Northern blots, Southern blots, and primer extension analyses indicated that ORF-1 and dbp comprised a two-gene operon located on the 49-kb linear plasmid. Both proteins, which were 40% identical and 56% similar, partitioned into Triton X-114 detergent extracts of B. burgdorferi isolated outer membranes. Mice infected with B. burgdorferi produced high titers of antibodies against the ORF-1-encoded protein and DBP during both early and later stages of chronic infection. Both DBP and the ORF-1-encoded protein were sensitive to proteinase K treatment of intact borreliae, suggesting that they were surface exposed. In active immunization experiments, 78% of mice immunized with recombinant DBP were immune to challenge. While it is not clear whether the two lipoproteins encoded by the ORF-1-dbp operon have analogous decorin-binding functions in vivo, the combined studies implicate DBP as a new candidate for a human Lyme disease vaccine.